Cordyceps cicadae NTTU 868 mycelium prevents CCl4-induced hepatic fibrosis in BALB/c mice via inhibiting the expression of pro-inflammatory and pro-fibrotic cytokines. (April 2018) - Ke, Bo-Jun; Lee, Chun-Lin
Graphical abstract: Highlights: C. cicadae NTTU 868 mycelium prevented CCl4 -induced liver fibrosis. Adenosine, HEA and polysaccharides prevented CCl4 -induced liver fibrosis. C. cicadae prevented liver fibrosis via TNF-α/IL-6 pathway, TGF-β1/CTGF pathway. Abstract: Hepatic fibrosis is caused by chronic liver injury and repeated repair with scar tissue accumulation in the liver. Cordyceps cicadae produces large quantities of adenosine, N6-(2-hydroxyethyl)-adenosine (HEA) and polysaccharides. This study investigated the effect of C. cicadae NTTU 868 mycelium and its bioactive compounds on carbon tetrachloride (CCl4 )-induced liver fibrosis. BALB/c mice were injected 0.5 µL/g CCl4 3 times weekly for 4 weeks to induce hepatic fibrosis and treated with C. cicadae NTTU 868 mycelium, adenosine, HEA, and polysaccharides daily for 6 weeks. CCl4 administration not only caused a remarkable liver damage but also resulted in abnormal collagen accumulation. C. cicadae NTTU 868 mycelium prevented CCl4 -induced hepatic fibrosis through TNF-α/IL-6 pathway, TGF-β1/CTGF pathway, and anti-oxidative defense mechanism. Although adenosine, HEA and polysaccharides performed protection against CCl4 -induced liver damage, HEA should be the main bioactive compound on the prevention of hepatic fibrosis in the C. cicadae NTTU 868 mycelium.